Analisis Perbedaan Sikap Kewirausahaan antara Suku Jawa dan Suku Madura di Wilayah Surabaya Selatan - Husni Indrawati Wijaya (Universitas Muhammadiyah Sidoarjo, 2017)
The objective of this research was to determine differences in entrepreneurial attitudes between Javanese and Madurese ethnic in the South Surabaya. This research is quantitative research by using independent sample t test analysis. The results on this research an entrepreneurial attitude Javanese higher than Madurese ethnic and there are significant differences between the entrepreneurial attitude Javanese and Madurese ethnic in South Surabaya area.